Digital Parenting and Socio-Emotional Development in Early Childhood: Evidence from Palu City, Indonesia - Kahar, M. Iksan; Wahyuningsih, Nur Eka; Anggraeni, Dewirini (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga, Yogyakarta, 2026)
Digital technology has become increasingly embedded in young children’s everyday lives, yet research on its developmental implications has often focused more on screen exposure than on the parental practices that shape children’s digital experiences. This study examined the relationship between digital parenting practices and the socio-emotional development of children aged 5 to 6 years in Palu City, Indonesia. Using a quantitative cross-sectional survey design, data were collected from 100 parents or primary caregivers selected through purposive sampling. The study employed structured questionnaires to measure digital parenting and children’s socio-emotional development, and the data were analysed using simple linear regression. The findings showed that digital parenting was positively and significantly associated with children’s socio-emotional development. The regression model produced an unstandardized coefficient of 0.583 and a standardized coefficient of 0.424, with the predictor reaching statistical significance at p < .001. The model explained 17.9% of the variance in socio-emotional development, indicating that digital parenting was relevant within the model but did not provide an exhaustive account of the outcome. These findings suggest that parental mediation in children’s digital lives may matter not only in terms of supervision and control, but also as part of the relational conditions through which children encounter digital media. The study contributes to the global literature by extending evidence on digital parenting and early childhood development into an underrepresented non-Western context, while also showing the need for more robust designs, more differentiated measures of mediation, and broader explanatory models in future research.